Study of the process of mix preparation using modified silicate connectings - D. M. Kukuj; V. A. Skvortsov; N. V. Andrianov; N. B. Krutilin (Литьë и металлургия)
Тhе article shows, that using of binding material in liquid glass mix proportions increases their fastness and plastic properties.